Limnology of Merbok estuary, Kedah, Malaysia (Bangladesh Journal of Zoology, 2015)
Water quality in three different stations of Merbok estuary was investigated limnologically from October, 2010 to September, 2011. Water temperature, transparency and total suspended solids (TSS) varied from 27.45 - 30.450C, 7.5 - 120 cm and 10 -140 mg/l, respectively. Dissolved Oxygen (DO) concentration ranged from 1.22-10.8 mg/l, while salinity ranged from 3.5-35.00 ppt. pH and conductivity ranged from 6.35 - 8.25 and 40 - 380 ?S/cm, respectively. Kruskal Wallis H test shows that water quality parameters were significantly different among the sampling months and stations (p